(untitled) (Al-Academy, 2025)
The Kingdom’s Vision 2030 is keen to pay attention to human development and enhance efforts that match the results of the training process with the needs of the local labor market. Saudi girls are considered a strong element of the nation, so the Kingdom embraces their development, investing in their energies and enabling them to obtain all appropriate opportunities to build their future and contribute to the development of society and the economy. Industry in the current era is one of the most important pillars and pillars of the economic structure, and its industrial activity depends on the necessity of preparing trained technical personnel and human resources and developing them constantly to ensure the success and stability of the efficiency of this industry, through which it can contribute to advancing the wheel of development. Universities and educational institutions are considered the greatest common denominator in any comprehensive development process taking place in the Kingdom of Saudi Arabia, as they are primarily concerned with developing trained human resources to participate in advancing the wheel of production. The research aims to : Design a clothing production unit for work training according to the productivity of ready-made clothing factories. Measuring the degree of acceptance of specialists and trainees for the proposed design of the clothing production unit according to the productivity of ready-made clothing factories. Preparing the technical file for manufacturing the dress in the proposed production unit according to the productivity of the clothing factories. The search found : 1. There are statistically significant differences between the average scores of the trainees in the pre- and post-application of a clothing production unit for job training according to the productivity of ready-made clothing factories, in favor of the post-application. 2. There are statistically significant differences between the average scores of the trainees in the pre- and post-application of skill performance in favor of the post-application. The search recommended : 1. Benefiting from the results of designing the production unit for the clothing industry to encourage female students to open ready-made clothing projects. 2. Preparing training programs for female students and graduates in the field of clothing manufacturing to develop their knowledge and skills regarding this field and open job opportunities for them. 3. Encouraging female students and graduates to participate in community service to train girls in school classes on the principles of knitting techniques in a scientific manner under institutional supervision.